Adhesive Hemostatic Conducting Injectable Composite Hydrogels with Sustained Drug Release and Photothermal Antibacterial Activity to Promote Full‐Thickness Skin Regeneration During Wound Healing. Issue 12 (20th February 2019) - Liang, Yongping; Zhao, Xin; Hu, Tianli; Chen, Baojun; Yin, Zhanhai; Ma, Peter X.; Guo, Baolin
Abstract: Developing injectable nanocomposite conductive hydrogel dressings with multifunctions including adhesiveness, antibacterial, and radical scavenging ability and good mechanical property to enhance full‐thickness skin wound regeneration is highly desirable in clinical application. Herein, a series of adhesive hemostatic antioxidant conductive photothermal antibacterial hydrogels based on hyaluronic acid‐graft‐dopamine and reduced graphene oxide (rGO) using a H2 O2 /HPR (horseradish peroxidase) system are prepared for wound dressing. These hydrogels exhibit high swelling, degradability, tunable rheological property, and similar or superior mechanical properties to human skin. The polydopamine endowed antioxidant activity, tissue adhesiveness and hemostatic ability, self‐healing ability, conductivity, and NIR irradiation enhanced in vivo antibacterial behavior of the hydrogels are investigated. Moreover, drug release and zone of inhibition tests confirm sustained drug release capacity of the hydrogels. Furthermore, the hydrogel dressings significantly enhance vascularization by upregulating growth factor expression of CD31 and improve the granulation tissue thickness and collagen deposition, all of which promote wound closure and contribute to a better therapeutic effect than the commercial Tegaderm films group in a mouse full‐thickness wounds model. In summary, these adhesive hemostatic antioxidative conductive hydrogels with sustained drug release property to promote complete skin regeneration are an excellent wound dressing for full‐thickness skin repair. Abstract : A series of hydrogel dressings with multifunctions including adhesive hemostatic antioxidative conductive photothermal antibacterial property based on hyaluronic acid‐graft‐dopamine and reduced graphene oxide (rGO) with a H2 O2 /HPR (horseradish peroxidase) system is prepared and the high promotion repair effect for full‐thickness skin wound regeneration confirms their great potential for clinical application.